Acute pancreatitis associated with hemorrhagic fever with renal syndrome: clinical analysis of 12 cases. (21st August 2013) - Fan, Heng; Zhao, Yu; Song, Fu-Chun
Abstract: Background : Acute pancreatitis is one of the rare complications of hemorrhagic fever with renal syndrome (HFRS), which easy to be misdiagnosed as acute abdomen, usually critically ill, poor treatment effect, highly mortality. In this study, we retrospectively analyzed to explore the clinical characteristics, 12 cases of hemorrhagic fever with renal syndrome complicated with acute pancreatitis treatment methods and prognosis. Methods : We conducted a retrospective study of HFRS in patients complicated with acute pancreatitis. 12 cases were collected from Ningbo first hospital between January 2001 and December 2012. Clinical information and laboratory parameters were obtained by reviewing literature and records. Results : Twelve from 156 cases (7.69%) HFRS complicated with acute pancreatitis. Men comprised more than half (75%) of the sample population, the mean age was (38 ± 19) years. Abdominal pain was the main clinical manifestations in all the patients, all of their serum amylase and serum lipase were increased, 10 patients were given the total abdomen CT examination, eight cases showed enlargement of the pancreas and surrounding leakage, two cases showed pancreatic necrosis and hemorrhage. Three cases complicated with pulmonary edema. In 12 cases, four of them received hemodialysis treatment, one gives surgical intervention. Eight cases were complete remission, three cases were partial remission and one case was death. Conclusions : Acute pancreatitis is one of rare of the serious complications of HFRS, whereas the correct diagnosis and clear the cause of disease is critical for improve the quality of life of patients and reduce the mortality, timely hemodialysis treatment is effective, early intervention can improve the prognosis.